Acts of the General Assembly of the State of Georgia Passed in Milledgeville at an Annual Session in November and December 1837, at 90-91 (1838) - (:unkn) unknown (My University, 1837)
§§ 1-4: Prohibited any merchant, or "any other person or persons whatsoever," to sell, offer to sell, keep, or have on their person or elsewhere any Bowie knife or "any other kind of knives, manufactured and sold for the purpose of wearing, or carrying the same as arms of offence or defence," pistols, swords, sword canes, or spears. Exempted "such pistols as are known as horseman's pistols" from these restrictions. Punishable by a fine of up to $100-500 for the first offense and $500-1,000 for subsequent offenses.
Keywords: TRANSFER, MANUFACTURE & POSSESSION